Strategi Pembelajaran Tematik Di Sekolah Dasar Negeri Pengawu - Muhammad Mansyur Thalib (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
The focuses of this research were the condition of instruction and strategy of instructional. The aim of this research was descriptif and explane the focuses. Data resource are: informan, process, setting, and document. The data collected was analysed by interactive analyses model. The instructional objective it stated by the basic competence and the indicators, sum of classes more then of classroom, media and funding were limited, few state teachers available, motivation and prior knowledge was different. The teacher was not desained instruction, the summary was carried out and tried to make analogy. The teachers was carried out by using of instructional media and maximaze the student interaction with the media. The learning schedule started earlier that is 07.10 and terminate by longer is 14.10. The progress records on the students used to developed based competence and motivational through by verbal or non-verbal methods.